Defects and Disabilities of Thalidomide Children. Issue 5848 (3rd February 1973) - Smithells, R. W.
Abstract : The range of defects and disabilities in thalidomide children is very much wider than is generally realized. The defects of 154 children are described and classified. Their disabilities range from incapacitating to negligible.